The location of starch in rubberwood / Ahmad Fauzi Othman, Rudaini Mohd Nawawi and Suhaimi Muhammed - Othman, Ahmad Fauzi; Mohd Nawawi, Rudaini; Muhammed, Suhaimi (2004)
Rubberwood (Hevea brasiliensis) contains substantial amount of starch, especially in the sapwood portion of the tree. This has been proven by iodine test whereby sapwood turns darker blue in colour but heartwood becomes lighter blue. The exact location of starch in rubberwood has not been studied in detail especially at the microscopic level of wood cells. This paper is an attempt to discover the nature and location of starch with the aid of light transmission microscope and scanning electron microscope (SEM). Interestingly, starch was observed in ray parenchyma and wood parenchyma cells. All wood parenchyma cells contain starch but only the upright cells of the ray parenchyma reveal the presence of starch. The nature of starch was either spherical or pear-like and pea-like shapes.